Development of E-Book Media to Foster Traffic Awareness in Early Childhood - Firda Alfira Muklis; Asep Kurnia Jayadinata; Risty Justicia; Dhea Ardiyanti; Lily Muliana Mustafa (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
Traffic awareness is an important aspect that needs to be instilled from an early age, as children are among the most vulnerable groups to road accidents. This study aims to design an e-book entitled “Let’s Get to Know Traffic Signs” as a learning medium for traffic awareness education in early childhood, intended for use by teachers. The method used is Educational Design Research (EDR), which includes three main stages: analysis and exploration, design and construction, and evaluation and reflection. Data were collected through interviews with early childhood education teachers, validated by media and content experts, and implemented through the traffic awareness e-book. The study was conducted at School X in Sukajaya District, Bogor Regency. The result of this development is an e-book that is considered suitable for early childhood. The validation process involved media and educational content experts using validation questionnaires and usability testing. The research involved 30 students in early childhood education. The findings demonstrate that the e-book, based on expert validation and its application with students, is a feasible educational medium for building traffic awareness in early childhood.